A Case of Paroxysmal Kinesigenic Dystonia : Epilepsy Mimic (Bangladesh Journal of Neuroscience, 2017)
Background: We report a rare case of movement disorder Paroxysmal kinesigenic dystonia who was misdiagnosed as Epilepsy and Conversion disorder.Case report: A 35 -year female presented with episodic painful twisting of her Right hand and arm only when she is awake. These events were triggered by sudden movements and would last several seconds to minutes. Her symptoms were unilateral and her physical and neurological examinations were normal. Treatment with anticonvulsants Oxcarbazepine improved her symptoms.Conclusion: Although an uncommon movement disorder, it is important to recognize the clinical presentation of Paroxysmal kinesigenic dystonia as most patients respond very well to medical treatment.Bangladesh Journal of Neuroscience 2017; Vol.  33 (1): 44-46